Health Equity and Future Public Health Interventions: Strategies for Reducing Disparities - Hoseini, Marjan Sadat (Journal of Foresight and Health Governance, 2024)
This study examines current public health interventions for reducing health disparities and explores future strategies that leverage technology, policy reforms, and community-driven approaches to achieve health equity. A narrative review with a descriptive analysis method was conducted, synthesizing recent literature, policy documents, and public health reports published between 2020 and 2025. The study analyzed the effectiveness of existing health equity strategies, including universal healthcare policies, community-based interventions, and digital health solutions. Key themes were identified through qualitative thematic analysis, focusing on healthcare financing models, artificial intelligence in disease surveillance, and cross-sector collaborations. The review highlights the effectiveness of universal healthcare expansion, culturally competent community-based programs, and telemedicine in addressing disparities. AI-driven predictive analytics and wearable health monitoring technologies are emerging as valuable tools in early disease detection and resource allocation. However, structural barriers, including fragmented healthcare systems, digital health inequities, and financial constraints, continue to hinder progress. Policy reforms that integrate social determinants of health, alongside sustainable healthcare financing models, are critical for reducing disparities. Additionally, participatory governance and community-led interventions have shown promise in improving long-term health outcomes. Health disparities persist despite ongoing interventions, requiring innovative, equity-focused public health strategies. Future efforts must emphasize sustainable universal healthcare models, the ethical integration of AI in public health, and strengthened cross-sector collaboration. Digital health solutions must be expanded with a focus on accessibility and equity to prevent the deepening of disparities. Long-term success in reducing health inequities will depend on adaptive policy reforms, participatory health governance, and the responsible application of emerging technologies.